2020
DOI: 10.1177/2158244020973021
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and Sustainable Development: Does Aid and Political Instability Impede Innovation?

Abstract: Sound innovation capabilities help the nations not only to capture bigger market shares but also to sustain long-term economic growth. Innovation is of vital importance at all stages of a country’s development as it promotes productivity, value creation, employment, economic growth, and sustainability. Several factors can affect the innovation activities of a country. For example, peaceful and stable environment, effective macroeconomic designs, sound institutional quality, and efficient utilization of resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 149 publications
(193 reference statements)
1
15
0
Order By: Relevance
“…Political instability has also been found to influence attracting foreign direct investments, which is often key to innovativeness in organizations (Shumetie and Watabaji, 2019). Nadeem et al (2020) found that the short- and long-run impacts of aid, political instability and terrorism in Pakistan harmed innovation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Political instability has also been found to influence attracting foreign direct investments, which is often key to innovativeness in organizations (Shumetie and Watabaji, 2019). Nadeem et al (2020) found that the short- and long-run impacts of aid, political instability and terrorism in Pakistan harmed innovation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Our results show that a 1 percent increase in macroeconomic instability will decrease the advancement of ICT by (0.155289) percent. In the presence of an unstable macroeconomic environment, an economy is unable to make much and sufficient expenditures on the advancement of ICT, thus, an unstable macroeconomic environment discourages the advancement of ICT (Kapurubandara & Lawson, 2006;Nadeem et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The estimated results show that the availability of physical capital has a positive and significant impact on the advancement of ICT (Ali, 2015;Ali & Rehman, 2015;Barro, 2013;Gokal & Hanif, 2004;Sidrauski, 1967). The results show that there is a negative and significant relationship between macroeconomic instability and the advancement of ICT (Kapurubandara & Lawson, 2006;Nadeem et al, 2020). The findings related to physical capital and macroeconomic instability are in line with the findings of the aggregate globalization model for the whole sample countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet the extant research shows that this learning (e.g. via R&D activities and technology-market knowledge transfer) is typically less efficient in regions characterized as politically unstable (Allard et al, 2012;Liao and Yu, 2012;Nadeem et al, 2020). This is because PI is likely to result in a deficiency of information (Todeva and Knoke, 2005), uncertainty and mistrust in the integrity of rules and regulations, and a lack of reliability of market knowledge (Delios and Henisz, 2003).…”
Section: The Moderating Effect Of Perceived Political Instabilitymentioning
confidence: 99%